Taller de poesía amazónica para el mejoramiento de la capacidad crítica en comprensión de textos en estudiantes del quinto grado de secundaria Institución Educativa Mariscal Oscar R. Benavides Iquitos 2024 - Daza Ramos, Floresmina (2025)
The main objective of this research was to evaluate the effect of the Amazonian Poetry Workshop on the development of critical capacity for text comprehension among fifth-grade secondary students at the Mariscal Oscar Benavides Educational Institution in Iquitos during the year 2024. The methodology used was based on an evaluative approach, specifically through a univariate, longitudinal, quasi-experimental, and field design. The study population consisted of 480 students, of which a sample of 60 was selected to form the intervention and control groups. A written test was developed to measure critical capacity, which was subjected to expert evaluation, and the data were collected using a survey technique. The results concluded that the Amazonian Poetry Workshop had a notable effect on the development of critical capacity within the experimental group. Initially, both groups were observed to have a deficient critical level; however, after the intervention, the experimental group reduced its percentage of students in the deficient category from 100.0% to 53.1%, accompanied by significant increases in the regular and good categories. These findings demonstrate a tangible improvement in the critical capacity of students who attended the workshop, supporting its effectiveness as a pedagogical tool and confirming the general hypothesis that the workshop facilitates the development of critical skills in reading comprehension.